The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.18632/oncotarget.25471
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of soluble urokinase plasminogen activator receptor (suPAR) predict outcome after resection of colorectal liver metastases

Abstract: BackgroundIn colorectal cancer (CRC), the liver is the most common site of metastasis. Surgical resection represents the standard therapy for patients with colorectal liver metastases (CRLM). However, 5-year survival rates after resection do not exceed 50%, and despite existing preoperative stratification algorithms it is still debated which patients benefit most from surgical treatment. The soluble urokinase plasminogen activator receptor (suPAR) has recently evolved as a promising biomarker for distinct clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…Our data are in line with previous publications showing elevated suPAR serum levels in manifold cancers. Just recently, we demonstrated that concentrations of suPAR are elevated in patients with cholangiocellular carcinoma (CCA) [18] as well as in patients with pancreatic ductal adenocarcinoma (PDAC) [34] or colorectal cancer (CRC) [20]. Notably, serum concentrations of suPAR in our cohort of patients with NET are numerically very similar to those found in CCA, PDAC and CRC.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Our data are in line with previous publications showing elevated suPAR serum levels in manifold cancers. Just recently, we demonstrated that concentrations of suPAR are elevated in patients with cholangiocellular carcinoma (CCA) [18] as well as in patients with pancreatic ductal adenocarcinoma (PDAC) [34] or colorectal cancer (CRC) [20]. Notably, serum concentrations of suPAR in our cohort of patients with NET are numerically very similar to those found in CCA, PDAC and CRC.…”
Section: Discussionsupporting
confidence: 70%
“…suPAR was identified as a biomarker in patients with inflammatory and infectious diseases [ 13 , 14 , 15 , 16 ]. Moreover, a prognostic role for suPAR serum levels has been demonstrated in different cancers including pancreatic, cholangiocellular and colorectal malignancies [ 17 , 18 , 19 , 20 ]. However, in NET no data on a potential role of circulating suPAR as a biomarker for prediction of patients’ prognosis or response to therapies have been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…12 SuPAR might also be an interesting circulating biomarker as recently shown for patients with sepsis 13 and cancer. [14][15][16] In BTC, preliminary data described a correlation between high tumoral uPAR expression and tumor invasion and metastasis. 17,18 However, there is insufficient data on a potential role of circulating suPAR as a biomarker in patients with BTC.…”
Section: Introductionmentioning
confidence: 99%
“…In liver malignancies, induction of uPAR was observed in colorectal liver metastases, whereas normal liver tissues showed very weak uPAR staining. However, serum suPAR levels increased after surgical resection of the tumor, suggesting that liver metastases are not a major source of circulating suPAR …”
Section: Cellular Source Of Supar In Liver Diseasementioning
confidence: 99%
“…They found that patients with suPAR levels >9.5 ng/mL at the beginning of the study progressed earlier to HCC; thus, they suggested that serum suPAR serves as a potential screening tool for the early diagnosis of HCC in patients with chronic liver disorders . In terms of liver metastases, Loosen et al measured suPAR levels in 104 patients undergoing hepatic resection for colorectal liver metastases. They found that the preoperative, but not postoperative, suPAR level was a prognostic factor for mortality.…”
Section: Elevation Of Supar Levels In Liver Diseasementioning
confidence: 99%